PENGEMBANGAN MEDIA PEMBELAJARAN MENGGUNAKAN APLIKASI BENIME BERBASIS PROBLEM BASED LEARNING PADA MATA PELAJARAN MATEMATIKA MATERI PECAHAN - Lala Aulia Hutagalung (JURNAL PENDIDIKAN DAN PEMBELAJARAN TERPADU (JPPT), 2022)
This development research aims to develop learning media using a problem-based learning application based on problem-based learning in mathematics subjects with fractions in class VI that are suitable for learning. This research is a type of research and development using the ADDIE development model. In this study, the researcher only carried out the ADDIE development model only to the development stage, because the focus of this research was only to develop learning media using an appropriate problem-based learning benime application that was suitable for use in the learning process. The instrument used to collect data is a questionnaire or questionnaire given to validators, namely material review expert validators, material expert validators and learning expert validators. Based on the validation results from the material review expert validators, a percentage of 55% was obtained, after the learning media using the revised problem based learning benime application obtained a percentage of 87% from the material review expert validators. From the results of the media expert validation, the percentage was 57%, after the learning media using the revised Benime-based application obtained a percentage of 80%. From the results of the validation of learning experts obtained a percentage of 84% without any revision. According to the assessment score criteria, it can be said that this development aims to develop learning media using the Benime-based problem-based learning application in the mathematics subject matter of fractions developed Very Valid/Very Appropriate for use in the learning process.